Moral Panics and Body Cameras - Howard M. Wasserman (Washington University Law Review, 2015)
This Commentary uses the lens of "moral panics" to evaluate public support for equipping law enforcement with body cameras as a response and solution to events in Ferguson, Missouri in August 2014. Body cameras are a generally good policy idea. But the rhetoric surrounding them erroneously treats them as the single guaranteed solution to the problem of excessive force and police-citizen conflicts, particularly by ignoring the limitations of video evidence and the difficult questions of implementing any body camera program. In overstating the case, the rhetoric of body cameras becomes indistinguishable from rhetoric surrounding responses to past moral panics.
Keywords: Ferguson; Ferguson Missouri; Body cameras; Police body cameras; Civil Rights Law; Police brutality; Michael Brown